Esoteropolitics, violence and armed conflict in Colombia—Narratives, actors and strategies - Niño, César; Guerrero-Sierra, Hugo; Wilches, Jaime (Frontiers in Political Science, 2025)
Esoteric practices have played a significant yet often overlooked role in shaping the dynamics of Colombia's armed conflict. This article introduces the concept of esoteropolitics to analyze the interplay between war, power, and supernatural rituals—including witchcraft, religion, spiritualism, and the occult. Using an intentional sampling strategy, 150 sources—comprising scientific articles, literary works, and journalistic records—were collected and systematically coded. The analysis focused on both macro and micro scenarios, tracing how objective and subjective narratives intersect in the conflict. Findings show that esoteropolitical elements were not only present but acted as influential agents throughout the conflict. Despite being systematically marginalized by political elites and illegal armed actors, esoteric narratives shaped war strategies, tactical decisions, and the formation of legitimacy and territorial control. This research expands the literature on the political functions of esotericism by demonstrating its embeddedness in armed conflict and its capacity to structure power relations. It urges a reconsideration of these often-invisible forces in understanding the logics of violence and governance in Colombia.